The power of resistance : culture, ideology and social reproduction in global contexts - Elmesky, Rowhea, 1975-; Yeakey, Carol Camp; Marcucci, Olivia C. (Bingley, U.K. : Emerald Publishing Limited, 2017)
Recent history has documented a phenomenal surge in global unrest. From Missouri to the Middle East, the world has watched waves of momentum build, peak, and dip around events such as the shooting of Michael Brown and the acquittal of Hosni Mubarak. There have been waves of mass protests of resistance, vivid expressions of human agency through the use of technology and social media, and the clear search for finding voice in spaces where the culture of silence has been the norm for decades. This quest for humanization has led, in some cases, to macro-level changes such as the fall of governments, the collapse of economic stability, and the production of immense refugee populations. It has also led to micro-level changes within individuals' decisions to no longer be silenced or accept the status quo. Although separated by vast geographic space, this book serves to link these struggles through developing understandings of common patterns within and interconnections across oppressive societal structures. While these dynamic forms of human agency can be studied from multiple perspectives, this book is guided through the powerful ideological frameworks of culture and social reproduction and looks specifically to the role of schooling as a vehicle for catalysing change.
Prelims -- Institutional and historical factors in inequality -- Students, youth, and families as agents of resistance -- Epilogue: the call for freedom -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Education -- History; History of education; Protest movements